A novel dual circulating fluidized bed technology for thermal treatment of municipal sewage sludge with recovery of nutrients and energy. (1st January 2023) - Peltola, Petteri; Ruottu, Lauri; Larkimo, Markus; Laasonen, Arttu; Myöhänen, Kari
Highlights: Integrated drying and combustion techniques allow viable treatment of sewage sludge. Resource recovery from sewage sludge highlights circular economy principles. First-of-its-kind industrial sludge combustion plant shows successful operation. Abstract: Sewage sludge (SS), a by-product of the wastewater treatment process, should be viewed not as waste, but as a potential resource for renewable energy and nutrient recovery. However, SS contains various toxic and harmful pollutants, e.g., pathogens, pharmaceutical residues, and microplastics. Through organic recycling and reuse of SS on land, these contaminants may leak into the environment, creating potential hazards to the ecosystem and human health. To tackle this issue, an advanced SS treatment technique within circular economy principles was proposed. In this process, mechanically dewatered SS with 20–25 % total solids is first dried at 110 °C in a circulating fluidized bed dryer and then combusted at 850 °C in a circulating fluidized bed reactor. Consequently, all the unwanted organic compounds are eliminated, and the ash – relatively high in nutrients and sufficiently low in heavy metals – can be further processed into fertilizers and used in forestry or farming. Moreover, the process is self-sufficient in terms of energy, enabling standalone operation without supplementary fuels, and providing excess heat that can be utilized, e.g., as district heat. This paper describes the process in detail and reviews experiences and lessons learned from the commissioning and trial operation of a newly erected 1.5 MWth sludge combustion plant with a throughput of 10 000 t/a. The operational performance of the plant has been verified based on continuous processing of dewatered SS, and the main operating parameters were consistent with design values. Therefore, the scale-up of this technique was considered both feasible and successful.